APLICACIÓN DE ESTRATEGIAS METODOLÓGICAS ACTIVAS Y SU INFLUENCIA EN LA COMPRENSIÓN LECTORA EN ESTUDIANTES DE 7MO GRADO DE EDUCACIÓN BÁSICA EN LA ESCUELA NICOLÁS VAZCONEZ DEL CANTÓN BABA PERÍODO 2024 - 2025. - PALACIOS RAMOS BRENDA KARINA (2024)
The present research was focused on the application of active methodological strategies and their influence on the reading comprehension of 7th grade students of basic education at the Nicolás Vázquez School. Reading comprehension is essential, not only for academic success, but also for integral development in society. The objective was to determine the influence of the application of active methodological strategies on the development of reading comprehension in 7th grade students of Basic Education at the Nicolás Vazconez school. The study had a quantitative, descriptive, explanatory, non-experimental approach, starting from the diagnosis of the domain of reading comprehension with a sample of 30 students and a survey of a teacher. The findings demonstrated the presence of deficiencies in the management of reading comprehension in its different components in a significant percentage of low level in the evaluated students, they do not have autonomy to summarize text, poor reading fluency, in the survey of teachers they work very little with active strategies, they have not received training for their implementation, they only sometimes apply reading aloud and do not work with technological tools due to lack of resources, they rarely evaluate children to know the shortcomings in reading, the results. Given the evidence, an alternative proposal is proposed that addresses several activities, concluding that active methodological strategies are a resource that teachers must use with the aim of promoting active participation and the development of reading comprehension related to the teaching-learning process.